The effect of antibiotics (Aureomycin-BI2 supplement) on weanling pigs on alfalfa pasture - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
Recently much has been written on the use of antibiotics in swine nutrition. Research has shown that different vitamin B12-antibiotic supplements stimulate gains in growing and fattening swine. Some problems, however, present themselves. First, is it necessary to feed the antibiotic supplement until the pig reaches market weight to get the full benefit of the stimulated gain, or does the stimulation resulting from feeding this supplement during early growth carryover into the fattening stage of the hog's development? Another problem that is apparent in the use of the B12-antibiotic supplement is the relative efficiency of the antibiotics in plant protein supplement diets and in mixed plant and animal protein supplement diets. Furthermore, is antibiotic feeding as effective with pasture-fed pigs as with dry lot-fed pigs? Experiments were conducted last summer and winter at this station with weanling pigs to determine some of the practical applications of antibiotic feeding. Lederle's Aurofac, the vitamin B12 and antibiotic feed supplement used in the experiments, was obtained from Lederle Laboratories Division, American Cyanamid Company, New York. It contained approximately 1.8 mg. of vitamin B12 and 1.8 grams aureomycin per pound. When mixed in the protein supplements, 3 pounds of Aurofac were used to each 100 pounds of the protein supplement. This amount was estimated to give the pigs about 0.5 percent of the aureomycin supplement in their total ration.
Keywords: Swine; Antibiotics; Alfalfa; Weanling pigs